Effect of EM propagation medium on electrorheological characteristics of dielectric nanofluids. Issue 4 (3rd April 2017) - Adil, Muhammad; Mohd Zaid, Hasnah; Chuan, Lee Kean; Ahmad Latiff, Noor Rasyada
ABSTRACT: The effect of dielectric loss on the electrorheological (ER) characteristic of dielectric nanofluids under shear was studied. When nanofluids are activated by an applied electric field, it behaves like a non-Newtonian fluid under ER effect by creating the chains of nanoparticles. ER characteristics of ZnO and Al2 O3 nanofluids with various nanoparticles concentration (0.1, 0.05, 0.01 wt%) were measured. For this purpose, a solenoid-based electromagnetic (EM) transmitter was used under different propagation media including air, tap water, and salt water. The result shows that all the nanofluids exhibit pseudo-plastic behavior, while the electric field causes a significant increase in viscosity in the presence of tap water, followed by salt water. Additionally, the viscosity of nanofluid shows a high dependence on particle loading. A possible mechanism was also proposed to describe the effect of dielectric properties on the ER behavior of dielectric nanofluids. GRAPHICAL ABSTRACT: